Exercise-induced inflammation alters the perception and visual exploration of emotional interactions - Keck, Johannes; Honekamp, Celine; Gebhardt, Kristina; Nolte, Svenja; Linka, Marcel; de Haas, Benjamin; Munzert, Jörn; Krüger, Karsten; Krüger, Britta; Justus Liebig University Giessen (My University, 2024)
Introduction: The study aimed to investigate whether an exercise-induced pro-inflammatory response alters the perception as well as visual exploration of emotional body language in social interactions. Methods: In a within-subject design, 19 male, healthy adults aged between 19 and 33 years performed a downhill run for 45 min at 70% of their VO2max on a treadmill to induce maximal myokine blood elevations, leading to a pro-inflammatory status. Two control conditions were selected: a control run with no decline and a rest condition without physical exercise. Blood samples were taken before (T0), directly after (T1), 3 h after (T3), and 24 h after (T24) each exercise for analyzing the inflammatory response. 3 h after exercise, participants observed point-light displays (PLDs) of human interactions portraying four emotions (happiness, affection, sadness, and anger). Participants categorized the emotional content, assessed the emotional intensity of the stimuli, and indicated their confidence in their ratings. Eye movements during the entire paradigm and self-reported current mood were also recorded. Results: The downhill exercise condition resulted in significant elevations of measured cytokines (IL6, CRP, MCP-1) and markers for muscle damage (Myoglobin) compared to the control running condition, indicating a pro-inflammatory state after the downhill run. Emotion recognition rates decreased significantly after the downhill run, whereas no such effect was observed after control running. Participants' sensitivity to emotion-specific cues also declined. However, the downhill run had no effect on the perceived emotional intensity or the subjective confidence in the given ratings. Visual scanning behavior was affected after the downhill run, with participants fixating more on sad stimuli, in contrast to the control conditions, where participants exhibited more fixations while observing happy stimuli. Conclusion: Our study demonstrates that inflammation, induced through a downhill running model, impairs perception and emotional recognition abilities. Specifically, inflammation leads to decreased recognition rates of emotional content of social interactions, attributable to diminished discrimination capabilities across all emotional categories. Additionally, we observed alterations in visual exploration behavior. This confirms that inflammation significantly affects an individual's responsiveness to social and affective stimuli.
Keywords: ddc:796